FOREIGN LANGUAGE ANXIETY IN OUT-OF-CLASS PERFORMANCE.IDENTIFYING LANGUAGE-ANXIETY SOURCES, ITS EFFECTS, AND COPING STRATEGIES - Morena, Katarzyna (Neofilolog, 2018)
Language researchers have long been aware that anxiety can be associated with the language learning process and negatively correlate with academic achievement, motivation and successful oral performance. Foreign language anxiety was first defined as a negative feeling associated with a language classroom and resulting from a fear of negative evaluation, tests and communication apprehension (Horwitz and Young, 1991). Some learners also reported that they experienced language anxiety in out-of-class oral performance, that it negatively affected their feeling of competence, and beliefs about their successful language acquisition, and also triggered physiological and cognitive responses. The research aimed at identifying sources of language anxiety and its manifestations in adult EFL learners in out-of-class settings, and a set of six strategies was proposed to help learners mitigate the feeling of foreign language anxiety.